Table of Contents - Stefanie Kremmel (Chronotopos)
The Cover presents a foto of the Memorial "Passages" created by Israeli artist Dani Karavan in Portbou in Catalonia. It honoros Walter Benjamin (1892-1940), who ended his life here.